Hospital nurse staffing and sepsis protocol compliance and outcomes among patients with sepsis in the USA: a multistate cross-sectional analysis - Dierkes, Andrew M; Aiken, Linda H; Sloane, Douglas M; Cimiotti, Jeannie P; Riman, Kathryn A; McHugh, Matthew D (BMJ open, 2022)
ObjectivesSepsis is a serious inflammatory response to infection with a high death rate. Timely and effective treatment may improve sepsis outcomes resulting in mandatory sepsis care protocol adherence reporting. How the impact of patient-to-nurse staffing compares to sepsis protocol compliance and patient outcomes is not well understood. This study aimed to determine the association between hospital sepsis protocol compliance, patient-to-nurse staffing ratios and patient outcomes.DesignA cross-sectional study examining hospital nurse staffing, sepsis protocol compliance and sepsis patient outcomes, using linked data from nurse (2015–2016, 2020) and hospital (2017) surveys, and Centers for Medicare and Medicaid Services Hospital Compare (2017) and corresponding MedPAR patient claims.Setting537 hospitals across six US states (California, Florida, Pennsylvania, New York, Illinois and New Jersey).Participants252 699 Medicare inpatients with sepsis present on admission.MeasuresThe explanatory variables are nurse staffing and SEP-1 compliance. Outcomes are mortality (within 30 and 60 days of index admission), readmissions (within 7, 30, and 60 days of discharge), admission to the intensive care unit (ICU) and lengths of stay (LOS).ResultsSepsis protocol compliance and nurse staffing vary widely across hospitals. Each additional patient per nurse was associated with increased odds of 30-day and 60-day mortality (9% (OR 1.09, 95% CI 1.05 to 1.13) and 10% (1.10, 95% CI 1.07 to 1.14)), 7-day, 30-day and 60-day readmission (8% (OR 1.08, 95% CI 1.05 to 1.11, p<0.001), 7% (OR 1.07, 95% CI 1.05 to 1.10, p<0.001), 7% (OR 1.07, 95% CI 1.05 to 1.10, p<0.001)), ICU admission (12% (OR 1.12, 95% CI 1.03 to 1.22, p=0.007)) and increased relative risk of longer LOS (10% (OR 1.10, 95% CI 1.08 to 1.12, p<0.001)). Each 10% increase in sepsis protocol compliance was associated with shorter LOS (2% ([OR 0.98, 95% CI 0.97 to 0.99, p<0.001)) only.ConclusionsOutcomes are more strongly associated with improved nurse staffing than with increased compliance with sepsis protocols.